Product design for manufacture and assembly - Boothroyd, G. (Geoffrey) (Marcel Dekker, 1994)
Presents a summary of the analytical tools used to evaluate the cost and difficulty of manufacturing and assembling proposed product designs, encouraging a continuous dialogue between designers and manufacturing engineers during the early stages of design.